Investigation on the stress behavior of cellulose acetate and the development of highly moisture‐resistant optical films for display devices. Issue 19 (27th July 2017) - Sang Park, Min; Jung, Seokwon; Jeong Heo, So; Geol Lee, Seung
ABSTRACT: An optical film with high optical anisotropy was prepared by the stretching of a cellulose acetate film and the consequential orienting of a retardation‐enhancing additive. The change in retardation in response to moisture absorption was explored and it was found that the degree of the retardation variation is strongly related to the stretching temperature. Stress generated by the stretching and its relaxation was systematically investigated to elucidate the effect of stretching temperature on the irreversible change in retardation upon moisture absorption. The results show that the magnitude of releasable stress plays an important role in controlling changes in optical properties. In addition, the difference in the deformation behavior between glassy and rubbery states should be taken into account in the development of a moisture‐resistant optical film. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2017, 55, 1470–1478 Abstract : Retardation of cellulose acetate film including a retardation‐enhancing additive is highly altered after the moisture absorption. The magnitude of the variation is highly affected by the stretching temperatures, at which there is significant difference in the stress generation as well as deformation behavior. Releasable stress and different deformation behavior are responsible for the difference in moisture‐resistance.